2023
DOI: 10.1186/s12985-023-02188-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of E6 and E7 genes of human papillomavirus type 16 from central China

Ting Li,
Zhiping Yang,
Chunlin Zhang
et al.

Abstract: Background Persistent high-risk human papillomavirus (HR-HPV) infection is an important factor in the development of cervical cancer, and human papillomavirus type 16 (HPV-16) is the most common HR-HPV type worldwide. The oncogenic potential of HPV-16 is closely related to viral sequence variation. Methods In order to clarify the variant characteristics of HPV-16 E6 and E7 genes in central China, E6 and E7 sequences of 205 HPV‐16 positive samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…However, there were no reports of positive selection sites for HPV58 E6 in China [ 33 36 ]. No positive selection sites for HPV16 E6 and E7 genes have been reported in central China [ 37 ]. No positive selection sites for HPV52 E6 and E7 genes have been reported in central and Southwest China [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were no reports of positive selection sites for HPV58 E6 in China [ 33 36 ]. No positive selection sites for HPV16 E6 and E7 genes have been reported in central China [ 37 ]. No positive selection sites for HPV52 E6 and E7 genes have been reported in central and Southwest China [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the substitution of the positive selection site D32E in HPV16 E6 influences its antigenic epitopes, which may make it more difficult to detect by the immune system, thereby enhancing adaptability of HPV to the environment. In addition, Li et al [ 37 ] suggested that non-conservative substitutions of amino acids should be fully considered when developing therapeutic vaccines, such as H31Y, D32N, D32E, I34M, L35V, E36Q, L45P, N65S, and K75T in HPV16 E6. Chen et al [ 33 ] suggested that K93N in HPV33 E6, Q97L in HPV33 E7, R145K in HPV58 E6, and T20I in HPV58 E7 belong to ideal B-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%